2008
DOI: 10.1186/1471-2172-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis is decreased in diabetic mouse macrophages and is regulated by AMPK

Abstract: Background: Macrophages (MΦs) utilize macropinocytosis to integrate immune and metabolic signals in order to initiate an effective immune response. Diabetes is characterized by metabolic abnormalities and altered immune function. Here we examine the influence of diabetes on macropinocytosis in primary mouse macrophages and in an in vitro diabetes model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…AMPK-dependent signaling pathways that result in macropinocytosis are not defined. Several recent studies hint at possible links between AMPK activity and the formation of actin-mediated lamellipodium formation and macropinocytosis (38,39). Rac1, PI3K/Akt, protein kinase C, and myosin light chain kinase (MLCK), which have either been previously identified to be involved in EBOV entry and macropinocytosis and/or were identified in our CGA screen, are known to be phosphorylation targets downstream of AMPK activation (36,(78)(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK-dependent signaling pathways that result in macropinocytosis are not defined. Several recent studies hint at possible links between AMPK activity and the formation of actin-mediated lamellipodium formation and macropinocytosis (38,39). Rac1, PI3K/Akt, protein kinase C, and myosin light chain kinase (MLCK), which have either been previously identified to be involved in EBOV entry and macropinocytosis and/or were identified in our CGA screen, are known to be phosphorylation targets downstream of AMPK activation (36,(78)(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a role in regulating metabolism, recent studies have implicated AMPK activity in actin polymerization and the induction of macropinocytosis and phagocytosis (36)(37)(38)(39)(40). For instance, macrophages from diabetic mice have reduced macropi-nocytosis, and leptin-enhanced AMPK activity increased macropinocytosis (38). Another recent study implicated Rac1 as a mediator of AMPK-dependent phagocytosis (36).…”
mentioning
confidence: 99%
“…It is worth mentioning that the top pathway, macropinocytosis by growth factor, is selected exclusively by SEROP. Previous research (Guest et al ., ) has found evidence that this process is closely related to high‐calorie‐induced obesity in mice.…”
Section: Real Data Analysismentioning
confidence: 99%
“…142 Moreover, the reduction in neointimal formation observed in rats treated with ␤-lapachone, a potent antitumor agent that stimulates NAD(P)H:quinone oxidoreductase activity, was attributed to the LKB1-dependent activation of the AMPK. 143 The contribution of inflammatory cells to atherogenesis is well documented; however, although hypoxia stimulates the AMPK in activated monocytes, 144 and AMPK activation attenuates the lipopolysaccharide-induced expression of inducible NOS, 145 regulates macropinocytosis, 146 and reduces migration to stromal cell-derived factor, 147 surprisingly little is known about the control and consequences of AMPK activation in monocytes/macrophages. In a study not directed at atherosclerosis, it could be demonstrated that AMPK signaling is a potential potent counter regulator of inflammatory signaling pathways.…”
Section: Fisslthaler and Fleming Ampk In Endothelial Signaling 121mentioning
confidence: 99%